Rhetoric and Reality: A Critical Review of Language Policy and Legislation Governing Official Minority Language Use in Health and Social Care in Wales - Prys, Cynog; Hodges, Rhian; Roberts, Gwerfyl (Minorités linguistiques et société / Linguistic Minorities and Society)

(untitled) (Institut canadien de recherche sur les minorités linguistiques / Canadian Institute for Research on Linguistic Minorities, 2021)
A concerted attempt is being made by the Welsh Government to revitalize the Welsh language in Wales through language legislation and policy initiatives. This paper explores the political rhetoric and practical reality of these recent legislative developments, as they pertain to the health care sector. It offers a qualitative analysis of written evidence provided by key stakeholders during the consultation process on the new legally-binding requirements of Welsh Language Standards for health care providers in Wales. We argue that these meso-level service providers are critical linchpins within the health care system and that it is at the meso level that full tensions between the macro rhetoric and micro reality occur. This contribution highlights shortcomings and barriers to Welsh language service provision in health care in Wales and recommends the adoption of wide-ranging, holistic approaches to language planning that meet the language needs of patients outlined by the Welsh Government.